Resistance patterns and clinical outcomes of Klebsiella pneumoniae and invasive Klebsiella variicola in trauma patients. - John L Kiley (Public Library of Science (PLoS), 2021)
Recent reclassification of the Klebsiella genus to include Klebsiella variicola, and its association with bacteremia and mortality, has raised concerns. We examined Klebsiella spp. infections among battlefield trauma patients, including occurrence of invasive K. variicola disease. Klebsiella isolates collected from 51 wounded military personnel (2009-2014) through the Trauma Infectious Disease Outcomes Study were examined using polymerase chain reaction (PCR) and pulsed-field gel electrophoresis. K. variicola isolates were evaluated for hypermucoviscosity phenotype by the string test. Patients were severely injured, largely from blast injuries, and all received antibiotics prior to Klebsiella isolation. Multidrug-resistant Klebsiella isolates were identified in 23 (45%) patients; however, there were no significant differences when patients with and without multidrug-resistant Klebsiella were compared. A total of 237 isolates initially identified as K. pneumoniae were analyzed, with 141 clinical isolates associated with infections (remaining were colonizing isolates collected through surveillance groin swabs). Using PCR sequencing, 221 (93%) isolates were confirmed as K. pneumoniae, 10 (4%) were K. variicola, and 6 (3%) were K. quasipneumoniae. Five K. variicola isolates were associated with infections. Compared to K. pneumoniae, infecting K. variicola isolates were more likely to be from blood (4/5 versus 24/134, p = 0.04), and less likely to be multidrug-resistant (0/5 versus 99/134, p<0.01). No K. variicola isolates demonstrated the hypermucoviscosity phenotype. Although K. variicola isolates were frequently isolated from bloodstream infections, they were less likely to be multidrug-resistant. Further work is needed to facilitate diagnosis of K. variicola and clarify its clinical significance in larger prospective studies.